2013
DOI: 10.1371/journal.pone.0068907
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Transcriptome of the Human Endometrial Ishikawa Cancer Cell Line Induced by Estrogen, Progesterone, Tamoxifen, and Mifepristone (RU486) as Detected by RNA-Sequencing

Abstract: BackgroundEstrogen (E2) and progesterone (P4) are key players in the maturation of the human endometrium. The corresponding steroid hormone modulators, tamoxifen (TAM) and mifepristone (RU486) are widely used in breast cancer therapy and for contraception purposes, respectively.Methodology/Principal findingsGene expression profiling of the human endometrial Ishikawa cancer cell line treated with E2 and P4 for 3 h and 12 h, and TAM and RU486 for 12 h, was performed using RNA-sequencing. High levels of mRNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 67 publications
2
34
0
1
Order By: Relevance
“…P 4 has been shown to completely inhibit estrogen-induced epithelial cell proliferation and DNA synthesis which is in line with the functional clustering related with 'proliferation.' Moreover, a functional analysis of mifepristone responsive genes in Ishikawa cells identified a signaling pathway associated with adhesion and cellto-cell interactions (Tamm-Rosenstein et al 2013), which is in line with the term 'cell adhesion' we found. In relation to the over-represented TBFS analysis in the promoter regions of endometrial genes regulated by mifepristone, it is interesting that the cognate sequence for PGR was not over represented, suggesting that the transcriptional regulation exerted by the PGR is presumably mostly indirect.…”
Section: Endometrial Gene Expression Profile After Mifepristonesupporting
confidence: 84%
“…P 4 has been shown to completely inhibit estrogen-induced epithelial cell proliferation and DNA synthesis which is in line with the functional clustering related with 'proliferation.' Moreover, a functional analysis of mifepristone responsive genes in Ishikawa cells identified a signaling pathway associated with adhesion and cellto-cell interactions (Tamm-Rosenstein et al 2013), which is in line with the term 'cell adhesion' we found. In relation to the over-represented TBFS analysis in the promoter regions of endometrial genes regulated by mifepristone, it is interesting that the cognate sequence for PGR was not over represented, suggesting that the transcriptional regulation exerted by the PGR is presumably mostly indirect.…”
Section: Endometrial Gene Expression Profile After Mifepristonesupporting
confidence: 84%
“…By contrast, we noted comparable endometrial expression levels of PR and E6AP in both groups (Figure 7, A, D, and E). These aberrantly lower expression levels of BMI1, but not PR and E6AP, in failed pregnancy were well associated with reduced expression levels of PR-target genes including FOSL2, JUN, TGFB1, and IRS (18,19,23) (Figure 7F), indicating a close correlation between BMI1 and P4-PR nuclear signaling in human endometrium during early pregnancy.…”
Section: Discussionmentioning
confidence: 90%
“…As shown in Supplemental Figure 8, we first generated a BMI1-null mutant Ishikawa cell line utilizing the CRISPR/Cas9 knockout strategy. It is interesting to note that null mutation of BMI1 in Ishikawa cells significantly reduced the expression levels of PR target genes, such as TGFB1 and NPAS2 (18,19) (Figure 4B) and hampered PR transcriptional activity as well when assessed by a P4 response element (PRE)-luciferase reporter assay upon P4 challenge ( Figure 4C). In line with the in vivo observation that supplementation of exogenous P4 can partially correct implantation defects in Bmi1…”
Section: Bmi1 Facilitates Pr Binding To the Pre Of The Target Gene Prmentioning
confidence: 99%
“…As demonstrated by gene array profiling, these genes are related to cellular processes of DNA replication, cell-cycle progression, and cellular organization (12). Yet, the exact molecular mechanism by which tamoxifen exerts adverse effects on the uterus remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%